2010
DOI: 10.1177/1941738109357299
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Associated Muscle Cramps

Abstract: Context:Exercise-associated muscle cramps (EAMC) are a common condition experienced by recreational and competitive athletes. Despite their commonality and prevalence, their cause remains unknown. Theories for the cause of EAMC are primarily based on anecdotal and observational studies rather than sound experimental evidence. Without a clear cause, treatments and prevention strategies for EAMC are often unsuccessful.Evidence Acquisition:A search of Medline (EBSCO), SPORTDiscus, and Silverplatter (CINHAL) was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…That is, the cramp training may have adapted the proprioceptive sensors to forceful contractions in a shortened position, avoiding an imbalance between the inhibitory and excitatory drive -with pre-eminence of the latter. This would be in line with the neuromuscular theory of exercise induced muscle cramps proposed by Miller et al 4 According to this theory, muscle fatigue predisposes the muscle to cramp, as it further decreases the inhibitory drive of GTO and increases the excitatory drive from muscle spindles.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…That is, the cramp training may have adapted the proprioceptive sensors to forceful contractions in a shortened position, avoiding an imbalance between the inhibitory and excitatory drive -with pre-eminence of the latter. This would be in line with the neuromuscular theory of exercise induced muscle cramps proposed by Miller et al 4 According to this theory, muscle fatigue predisposes the muscle to cramp, as it further decreases the inhibitory drive of GTO and increases the excitatory drive from muscle spindles.…”
Section: Discussionsupporting
confidence: 87%
“…These idiopathic cramps often occur during prolonged intense contractile activity and are therefore commonly denominated as exercise-associated muscle cramps (EAMC). 4 Despite a potential overlap with the aforementioned acute depletion of the extracellular volume due to extensive sweating, it has been reported that 69% of the EAMCs occur in subjects that were well hydrated and sufficiently supplemented with electrolytes. 5 Therefore, it seems questionable if those factors are capable of explaining the development of EAMCs.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these results it is tempting to suggest that poor oral health may belong to the class of intrinsic risk factors for sports injuries labeled ‘health problems’ by Bahr and Krosshaug [ 4 ]. Support for this suggestion comes from studies showing that (1) poor oral health is also associated with chronically higher levels of IL-6 and other cytokines [ 10 - 13 ], that (2) chronically higher levels of IL-6 and other cytokines are associated with fatique [ 12 , 13 ] and that (3) fatique is a serious risk factor for (re)injuries [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the neuromuscular theory of exercise-associated muscle cramps, muscular fatigue is not only a risk factor but is a requirement for cramping [ 14 ]. Therefore, our finding that REAMC was associated with player position and with SumDental, indicates that both physical effort and poor oral health are associated with the development of muscular fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation